The Association of Frailty With Outcomes for Older Adults Undergoing Appendectomy. Issue 10 (October 2022) - Salzman, Garrett A.; Saliba, Debra; Ko, Clifford Y.; Maggard-Gibbons, Melinda; Russell, Marcia M.
Background: Frailty is a potential modifiable predictor of surgical outcomes in older adults. The impact of frailty following appendectomy, a common urgent operation, is unknown for older adults. The study aim was to assess if frailty is associated with worse perioperative outcomes after appendectomy in older adults. Methods: We used the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) database from 2016 to 2018 and identified patients 65 and older who underwent appendectomy for acute appendicitis. We identified frailty as a Modified Frailty Index (MFI) score ≥2. Multivariate logistic regression was used to assess the association of frailty with 30-day mortality, serious complications, readmission, and discharge to facility. Results: Five thousand seven hundred twenty-eight older adults underwent appendectomy, of which 29.1% were 75 or older, 53.3% female, 74.9% non-Hispanic White, and 17.1% frail. Frail patients experienced worse outcomes: mortality (frail: 1.0% vs non-frail: .3%, P = .001), serious complications (14.2% vs 8.0%, P = <.0001), and discharge to facility (9.3% vs 2.3%, P < .0001). On multivariate logistic regression, frailty was associated with increased mortality (odds ratio [OR] 3.34; 95% confidence interval [CI] 1.28-8.66), serious complications (OR 1.51; 95% CI: 1.17-1.93), and discharge to facility (OR 2.80; 95% CI: 2.00-3.93). Frailty was not significantly associated with readmission ( P = .180). Conclusions: Frailty is associated with worse postoperative outcomes following appendectomy in older adults. As frailty is potentially modifiable, it should be routinely assessed and utilized in perioperative optimization and counseling, especially with respect to patient-centered outcomes.